OPPORTUNITIES FOR THE MIDDLE-INCOME TRAP IN INDO-PACIFIC: A CASE STUDY OF INDONESIA [PELUANG JEBAKAN KELAS MENENGAH DI INDO-PASIFIK: KASUS DI INDONESIA] - Jane Sherly Stephanie (Universitas Pelita Harapan, 2021)
The term Middle-Income Trap (MIT) began to develop due to the growth rate of middle-income countries which had stagnated since 1980 (Pruchnik & Zowczak, 2017). This is due to the inability of a country to compete with high-income countries that are superior in technology, as well as low-income countries which are superior because they have cheap labour costs (Pruchnik & Zowczak, 2017). Indonesia as one of the MIT countries need to find a solution so that it does not continue to be trapped in it, the case experienced by Indonesia does not only threaten Indonesia to be caught in MIT's trap, but it can fall back into a low-income country (Basri & Putra, 2016). Therefore, Indonesia's role in the economic sector in the Indo-Pacific region is essential. The Indonesian government is expected to be able to use this opportunity to get out of the MIT trap as well as take advantage of the opportunities that exist to minimize the potential for Indonesia to fall back into a low-income country. In order to improve its economy, Indonesia can maximize the marine and fisheries sector or better known as the Blue Economy, including developing the marine tourism industry, such as increasing diving tourism destinations. Apart from that, the national leadership role is also significant and crucial, especially in strengthening the industrial sector (Basri & Putra, 2016). Using secondary data and case study methods, this paper will examine the opportunities that can be taken by Indonesia as an MIT country in the economic sector (especially the Blue Economy) in the Indo-Pacific region.Bahasa Indonesia Abstract: Istilah Middle-Income Trap (MIT) mulai berkembang karena laju pertumbuhan negara-negara berpenghasilan menengah yang mengalami stagnasi sejak tahun 1980 (Pruchnik & Zowczak, 2017). Hal ini disebabkan ketidakmampuan suatu negara untuk bersaing dengan negara-negara berpenghasilan tinggi yang unggul dalam teknologi, serta negara-negara berpenghasilan rendah yang unggul karena memiliki biaya tenaga kerja yang murah (Pruchnik & Zowczak, 2017). Indonesia sebagai salah satu negara MIT perlu mencari solusi agar tidak terus terjebak di dalamnya, kasus yang dialami Indonesia tidak hanya mengancam Indonesia untuk terjebak dalam jebakan MIT, namun bisa jatuh kembali ke posisi terendah pendapatan negara (Basri & Putra, 2016). Oleh karena itu, peran Indonesia dalam sektor ekonomi di kawasan Indo-Pasifik sangat penting. Pemerintah Indonesia diharapkan dapat memanfaatkan peluang ini untuk keluar dari jebakan MIT serta memanfaatkan peluang yang ada untuk meminimalisir potensi Indonesia terjerumus kembali menjadi negara berpenghasilan rendah. Dalam rangka meningkatkan perekonomiannya, Indonesia dapat memaksimalkan sektor kelautan dan perikanan atau yang lebih dikenal dengan Blue Economy, termasuk mengembangkan industri wisata bahari, seperti memperbanyak destinasi wisata selam. Selain itu, peran kepemimpinan nasional juga signifikan dan krusial, terutama dalam penguatan sektor industri (Basri & Putra, 2016). Dengan menggunakan data sekunder dan metode studi kasus, tulisan ini akan mengkaji peluang yang dapat diambil oleh Indonesia sebagai negara MIT di sektor ekonomi (khususnya Blue Economy) di kawasan Indo-Pasifik.